Aço inoxidável duplex de baixa liga, S32101: uma visão tecnológica sobre resistência mecânica, impacto, corrosão localizada e microestrutura - Ferezin, Tiago Daniel (2021)
The applications of duplex stainless steels are growing steadily in fields such as the paper, foodstuff, chemical and petrochemical industries. However, one drawback is cost, mainly due to the presence of Ni and Mo. Recently, by the total or partial replacement of by N and Mn, both strong austenite stabilizers, the so-called lean duplex stainless steel´s family was developed. As a consequence of the new composition some properties are changed with respect to the conventional duplex steels, of which the S32205 is the most widely known. The present work is meant to be a comprehensive study of the S32101 steel, in which microstructure, tensile and impact properties, and corrosion behaviour in FeCl3.6H2O, were investigated on welded joints produced by the TIG process, in which two different heat inputs, 1.3 and 0.9 kJ/mm, were employed. Additionally, the weld cooling rate was measured in the ZTA and bending tests were performed. Results showed that the microstructure was almost unaffected by the weld cycle, regardless the cooling rate. In the ZTA the α/ ratio was larger than one, and in the weld metal was slightly biased towards austenite. A fine precipitation of Cr2N was detected in the ferritic regions of the ZTA’. Tensile strength of the welded joint was higher than that of the S32205 steel, with the fracture always taking place in the weld metal. The impact energy of the weld metal produced with the higher heat input (sample AA) was equal to 72 J, that is, almost 85% higher than that of sample BA. However, the ZTA impact energy was much lower and was unaffected by the different heat inputs. The fracture surfaces show weld metal with normal appearance, that is, shear lips and brittle areas, base metal with delaminations, and ZTA with similar features, suggesting that the crack, originally located in the ZTA, may have been deflected towards the base metal. As for the corrosion behaviour, although pits were observed main along the ZTA of both samples, the one with the higher heat input was more affected.